Evangelicalism and dissent in modern England and Wales
1 online resource.
Keywords: "This book treads new ground by bringing the Evangelical and Dissenting movements within Christianity into close engagement with one another. While Evangelicalism and Dissent both have well established historiographies, there are few books that specifically explore the relationship between the two. Thus, this complex relationship is often overlooked and underemphasised. The volume is organised chronologically, covering the period from the late seventeenth century to the closing decades of the twentieth century. Some chapters deal with specific centuries but others chart developments across the whole period covered by the book. Chapters are balanced between those that concentrate on an individual, such as George Whitefield or John Stott, and those that focus on particular denominational groups like Wesleyan Methodism, Congregationalism or the 'Black Majority Churches'. The result is a new insight into the cross pollination of these movements that will help the reader to understand modern Christianity in England and Wales more fully. Offering a fresh look at the development of Evangelicalism and Dissent, this volume will be of keen interest to any scholar of Religious Studies, Church History, Theology or modern Britain"--